Model Problem Based Learning dengan Media Power Point untuk Meningkatkan Minat dan Kemampuan Pemecahan Masalah Matematika Siswa - Lastri, Fitriatun; Nissa, Ita Chairun; Yuliyanti, Sri (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This study aims to describe the application of the problem-based learning model with power point media in increasing interest and ability to solve math problems for class XI students at MA Plus Nurul Islam Sekarbela. The method used in this research is classroom action research which has four stages: action planning, action implementation, data observation and reflection. Data collection techniques in this study were test techniques, questionnaire techniques, observation techniques and documentation techniques, while the instruments in this study were test instruments, questionnaires and observation sheets. The results showed that students' interest in learning mathematics was high with a score of 80.13% in both cycle I and cycle II. Students' mathematical problem solving abilities also increased from cycle I to cycle II, namely 45.6% (enough) to 80.6% (high). This increase in interest and learning outcomes was supported by the average learning observation results in cycle I of 89% (very high) which increased in cycle II to 99.33% (very high). Based on the results of this study, it can be said that the application of the Problem Based Learning model with Power Point media can be used as an alternative learning to increase students' interest and ability to solve mathematical problems in class XI MIPA at MA Plus Nurul Islam Sekarbela.